In situ catalytic fast pyrolysis of paddy husk pyrolysis vapors over MCM-22 and ITQ-2 zeolites - Naqvi, S.R. (Elsevier B.V., 2015)
Non-catalytic and catalytic fast pyrolysis of paddy husk was performed with a medium pore framework zeolite (MCM-22) and its delaminated counterpart with a higher external surface area (ITQ-2) using a lab scale fixed-bed reactor. This work investigates the influence of the catalyst physical structure on the yields of gas, liquid and solid products and gas composition. The maximum pyrolysis oil yield of 34.8 (water 15.1 , organics 19.7) was obtained at 450 Â°C. At this temperature, catalytic pyrolysis was carried out using MCM-22 and ITQ-2. A mixture of 10 grams of rice husk and a prescribed amount of catalyst (0.5, 1 or 5 g) was used for catalytic pyrolysis. By using catalysts, the pyrolysis oil yield decreases. This decrement in pyrolysis oil yield is attributed to catalytic cracking of pyrolysis oil vapor on the catalyst. Decarbonylation and decarboxylation were identified as the major reactions in this cracking. Comparison of results for MCM-22 with ITQ-2, ITQ-2 culminated in slightly higher pyrolysis oil yield than those of MCM-22. This may be attributed to ITQ-2's thinner delaminated structure compared to MCM-22. Thinner structure makes the reactants (molecules of pyrolysis oil) more accessible to the catalytic sites and let the products (upgraded molecules generated from pyrolysis oil) leave from the catalytic sites to the bulk faster. ITQ-2 possessed high acid active sites and large external surface area which were responsible for high deoxygenation of oxygenated species and enhanced the production of aromatic hydrocarbons. Â© 2015 Elsevier B.V. All rights reserved.